PENGARUH PENGGUNAAN METODE CERAMAH BERKOMBINASI TERHADAP HASIL BELAJAR MATA PELAJARAN MEKANIKA TEKNIK SISWA JURUSAN TEKNIK BANGUNAN SMK NEGERI 1 TANJUNG RAYA - 661-670, Zulafatah Ahmad (CIVED, 2015)
Abstract This research is motivated by the low student learning outcomes in subjects Mechanics , in class X Architecture Engineering taught by subject teachers to use the lecture method. This study aims to determine whether there is a difference in student learning outcomes are taught using lecture method in accordance with the study of theory and opinion of the experts with regular lecture method applied by teachers on the subjects of Mechanics, students majoring in construction engineering SMK Negeri 1 Tanjung Raya. This type of research is experimental research with nonequivalent control group design. The population of this research is all class X students at the Department of Building Engineering SMK 1 Tanjung Raya with the division of a sample of 20 students of class X Architecture Engineering as the control group and 20 students of class X Mechanical Work Wood as sample experimental group. Instrument data retrieval using 29 test items that have been analyzed objective validity . Data analysis is done by using the t test. Based on the description of the data showed that the average learning outcomes in the experimental group at 84.40 is higher than student learning outcomes in the control group at 76.65. in accordance with the results of research confirming the hypothesis is accepted then it indicates that the use of combined methods appropriate to the study of the theory proved to be effective, hypothesis is accepted at significance level of 95 %.   Key words : influence , teaching methods lectures , learning outcomes